Two new species of Fridericia (Annelida: Enchytraeidae) from Hungarian caves - Dózsa-Farkas, Klára; Nagy, Hajnalka; Felföldi, Tamás (European Journal of Taxonomy, 2019)
Cave research in Hungary has developed a lot in the last decade. As a part of this progress, enchytraeid specimens were collected from Hungarian caves and were subsequently characterized by comparative morphological and molecular taxonomic analyses. Molecular phylogenetic studies based on ITS, CO1 and H3 sequences and morphological results confirmed that these specimens represented two species new to science. The descriptions of Fridericia baradlana sp. nov. and Fridericia spelaeophila sp. nov. are presented in this paper.